Nursing care for patients with venous ulcers treated at a University Hospital: Experience report - Ribeiro, Aclênia Maria Nascimento (2021)
Introduction: Among the chronic diseases that most affect adults are chronic venous ulcers, which are considered a syndrome that causes tissue loss, capable of reaching the subcutaneous and adjacent tissue, especially in the extremities of the lower limbs. These lesions can remain for a long time and have a frequent recurrence, taking from months to years, for tissue epithelialization to occur. Methodology: This is an experience report that describes aspects experienced by nursing residents, in the opportunity to enter a Multiprofessional Residency Program in Health at a Federal University of the Northeast, whose practical activities were developed in different sectors of a university hospital, including the stomatherapy outpatient clinic. Results and discussions: The activities developed by the residents in the stoma therapy outpatient clinic were diverse and varied from the dressing to welcoming the patient in nursing consultations, providing guidance for self-care and the correct management of venous ulcers, encouraging healthy eating. and maintenance of treatment and support for patients and family members, thus allowing comprehensive care. Conclusion: Thus, it is believed that the experience allowed the consolidation of theoretical and practical knowledge, gain of autonomy, development of skills and manual dexterity during the dressing, evaluating and investigating the physical and systemic aspects that interfere in the healing process, and yet, it was a favorable opportunity for the application of SAE on an outpatient basis.